Impact of waiting time on nodal staging in head and neck squamous-cell carcinoma treated with radical intensity modulated radiotherapy. (December 2016) - Chevalier, Cédric; Bertaut, Aurélie; Quivrin, Magali; Vulquin, Noémie; Desandes, Cédric; Folia, Mireille; Duvillard, Christian; Truc, Gilles; Crehange, Gilles; Maingon, Philippe
Abstract: Background and purpose: To evaluate the influence of delays for radiotherapy on survival, recurrence and upstaging for head and neck squamous-cell carcinoma (HNSCC) with no nodal involvement treated with intensity modulated radiotherapy (IMRT). Material and methods: This retrospective study included 63 consecutive patients with HNSCC located in the pharynx and larynx and treated with exclusive IMRT with or without chemotherapy. Survival, loco-regional or distant failure and upstaging were analyzed according to the waiting time. Results: Mean waiting time for treatment was 62.5 days for the hypopharynx subgroup (range = 37–102), 63 days for the larynx subgroup (range = 19–128) and 58.5 days for the oropharynx subgroup (range = 29–99) ( p  = 0.725). Nine patients (14%) experienced upstaging. Loco-regional or distant failure occurred in 18 patients. Beyond a delay of 50 days, 19% of patients had local failure, 17% nodal recurrence and 11% distant failure. Within a delay of 50 days, no nodal or distant failure was observed and only 1 patient experienced local recurrence. Upstaging and overall survival were not significantly affected by an increased waiting time. Conclusion: For N0 patients treated with IMRT for HNSCC, waiting time around 50 days after the diagnosis was not significantly associated with an excessive risk of upstaging or recurrence.